Choroidal osteoma with choroidal neovascular membrane: Successful treatment with intravitreal bevacizumab - Pandey, Neeraj (Dove Medical Press, 2010)
An otherwise healthy 27-year-old woman presented with complaints of sudden painless blurred vision in the right eye for one week. On examination, visual acuity was 20/30 in the right eye and 20/20 in left eye. Fundus examination OS was normal, but OD demonstrated an elevated, opaque, yellowish parapapillary choroidal lesion with grayish membrane associated with minimal subretinal fluid, suggestive of a choroidal neovascular membrane in the center. B-scan ultrasonography revealed findings consistent with a choroidal osteoma. Fundus fluorescein angiography of the right eye revealed a relatively well defined area of hyperfluorescence that increased in size and intensity in the later phases, suggestive of active extrafoveal choroidal neovascular membrane. Optical coherence tomography confirmed the extrafoveal choroidal neovascular membrane with subfoveal fluid. She was treated with intravitreal bevacizumab OD. At the two-week visit, vision OD improved to 20/20. Fluorescein angiography and optical coherence tomography revealed a resolved choroidal neovascular membrane. Intravitreal bevacizumab may be an effective alternative in the management of choroidal neovascular membrane secondary to choroidal osteoma.